Investigation of Cylinder Deactivation (CDA) Application on a Naturally Aspirated Engine - Zainal Abidin, Shaiful Fadzil; Khalid, Amir; Muhamad Said, Mohd Farid; Zahari, Izzarief; Abdul Jalal, Rifqi Irzuan (International Journal of Integrated Engineering, 2022)
Increasing oil prices and emission legislation have forced automotive company to investigate new methods and technologies to reduce the harmful effect produced from the motor vehicle, particularly CO2 (Carbon-Dioxide). A lot of studies and researches have been put into in order to achieve a zero emission vehicle with the usage of electricity rather than fossil fuel, but the challenge to cost and environmental effect makes an IC engine is still being the predominant power plant for automobile in this century. One of the popular techniques among engine manufacturers to have a better engine efficiency is cylinder deactivation. Cylinder deactivation is a promising method to reduce the fuel consumption and emission by forced the engine to operate at higher load. However, the higher combustion pressure and extreme temperature at firing cylinders will result in higher NOx composition. This paper will investigate further the engine performance, fuel economy and emission by using one-dimensional (1-D) simulation tool. A standard 1.6 litre naturally aspirated four in-line cylinders, port fuel injection engine is modelled and correlated to the measured test data. The model is then simulated with cylinder deactivation mode by deactivating the intake and exhaust valves at cylinders no 2 and no 3 as well as fuel injection at various engine speeds at part load conditions to show improvements in fuel consumption, CO2  emissions, pumping losses and effects on CO and NOx emission. This correlated model is then used to investigate the application of EGR in order to reduce the emission level. Also, the effects on in-cylinder combustion as well as pumping losses are presented. The study shows that the application of EGR is very significant for engine with CDA mechanism to ensure the overall engine fuel consumption and emissions are reduce simultaneously.